Peran Asbab Al-Nuzul dalam Kontekstualisasi Ayat Al-Qur’an - Andi Mujahidil Ilman SM (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2024)
Contextualization the verses of the Qur'an cannot be separated from the role of asbāb al-nuzūl in the process of interpretation. Asbab al-Nuzul of a verse is one of the lights to understand the meaning of the verse comprehensively. This type of research is library research and is descriptive qualitative, this research is carried out by referring to various literature related to the discussion, such as classic or contemporary literature, then analyzing the various literature to find the purpose of this research, namely to reveal the role of asbab al-nuzul in contextualizing the verse of the Qur'an. From the results of the research, it is found that asbāb al-nuzūl includes chronology, actors, and the time of an event, referring to this, the substance of meaning will be found by referring to the rules of khas and 'amm as formulated by scholars, based on these rules then become material for contextualizing verses in the present so that they can answer all life problems. Examples of the application of these rules such as the law of hand cutting is contextualized with prison law, and the testimony of four people on criminal charges to the context of CCTV footage.